Embracing the kindness in leadership / Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Regardless of our position, leadership is vital in all aspects of our life. The term leadership is more exhaustive than only focusing on the role between superiors and employees. Consequently, we need to be fair in everything that we do. In addition to being fair, kindness must be present because being fair alone is not enough to be a good leader. Sadly, we attend various leadership courses to become good leaders. However, those training becomes meaningless without adapting to the excellence criteria of leadership. We are just attending the training to fulfil the training hours required by our organization. The lines between work and personal can often be blurred due to the demanding of both responsibilities that we need to fulfil. We are expected to perform and carry out our responsibility diligently. However, it is easier said than done. Not all of us carry out the same responsibility, and our life has been influenced by many aspects such as psychological (food and clothing), safety (job security), love and belonging needs (friendship), self-esteem, and selfactualization, as mentioned by Maslow (1943).